FOXO3A acts as immune response modulator in human virus-negative inflammatory cardiomyopathy - Makrutzki-Zlotek, Kamila; Escher, Felicitas; Karadeniz, Zehra; Aleshcheva, Ganna; Pietsch, Heiko; Küchler, Konstanze; Schultheiss, Heinz-Peter; Heidecker, Bettina; Poller, Wolfgang; Landmesser, Ulf; Scheibenbogen, Carmen; Thevathasan, Tharusan; et al. (Heart (British Cardiac Society), 2023)
ObjectiveInflammatory cardiomyopathy is characterised by inflammatory infiltrates leading to cardiac injury, left ventricular (LV) dilatation and reduced LV ejection fraction (LVEF). Several viral pathogens and autoimmune phenomena may cause cardiac inflammation.The effects of the gain of function FOXO3A single-nucleotide polymorphism (SNP) rs12212067 on inflammation and outcome were studied in a cohort of patients with inflammatory dilated cardiomyopathy (DCMi) in relation to cardiac viral presence.MethodsDistribution of the SNP was determined in virus-positive and virus-negative DCMi patients and in control subjects without myocardial pathology. Baseline and outcome data were compared in 221 virus-negative patients with detection of cardiac inflammation and reduced LVEF according to their carrier status of the SNP.ResultsDistribution of SNP rs12212067 did not differ between virus-positive (n=22, 19.3%), virus-negative (n=45, 20.4 %) and control patients (n=18, 23.4 %), indicating the absence of susceptibility for viral infection or inflammation per se (p=0.199). Patients in the virus-negative DCMi group were characterised by reduced LVEF 35.5% (95% CI) 33.5 to 37.4) and increased LVEDD (LV end-diastolic diameter) 59.8 mm (95% CI 58.5 to 61.2). Within the group, SNP and non-SNP carriers had similarly impaired LVEF 39.2% (95% CI 34.3% to 44.0%) vs 34.5% (95% CI 32.4 to 36.5), p=0.083, and increased LVEDD 58.9 mm (95% CI 56.3 to 61.5) vs 60.1 mm (95% CI 58.6 to 61.6), p=0.702, respectively. The number of inflammatory infiltrates was not different in both SNP groups at baseline. Outcome after 6 months showed a significant improvement in LVEF and clinical symptoms in SNP rs12212067 carriers 50.9% (95% CI 45.4 to 56.3) versus non-SNP carriers 41.7% (95% CI 39.2 to 44.2), p≤0.01. The improvement in clinical symptoms and LVEF was associated with a significant reduction in cardiac inflammation (ΔCD45RO+ p≤0.05; ΔMac-1+ p≤0.05; ΔLFA-1+ p≤0.01; ΔCD54+ p≤0.01) in the SNP cohort versus non-SNP cohort, respectively. Subgroup analyses identified ΔMac-1+, ΔLFA-1+, ΔCD3+ and Δperforin+ as predictors for improvement in cardiac function in SNP-positive patients.ConclusionFOXO3A might act as modulator of the cardiac immune response, diminishing cardiac inflammation and injury in pathogen-negative DCMi.